Consideration of patient phenotypes in geographic atrophy due to age-related macular degeneration - Rishi P Singh; Roy Schwartz; Caroline R Baumal; Roger A Goldberg; John W Kitchens; Christina Y Weng; Jaclyn Quilantan (BMJ Open Ophthalmology)
Geographic atrophy (GA) is a form of advanced age-related macular degeneration (AMD) affecting approximately 1 million people in the USA and 5 million globally. In this review, retinal imaging techniques used for diagnosis and monitoring progression of GA in AMD, and the risk factors associated with the development and progression of GA are summarised. To familiarise clinicians with common phenotypes of patients with GA, the clinical and imaging features that may lead to rapid progression of GA in various phenotypes are highlighted. With the recent US Food and Drug Administration approval of new GA treatments that reduce lesion growth, understanding the risk of progression to GA and factors contributing to GA growth may aid in patient selection and guide patient-level management and treatment.